Demographic and dietary risk factors in relation to urinary metabolites of organophosphate flame retardants in toddlers. (October 2017) - Thomas, M.B.; Stapleton, H.M.; Dills, R.L.; Violette, H.D.; Christakis, D.A.; Sathyanarayana, S.
Abstract: Organophosphate flame retardants (OPFRs), including Tris (1, 3-dichloro-isopropyl) phosphate (TDCPP), triphenyl phosphate (TPP), and isopropylated triphenyl phosphate (ITP), are increasingly used in consumer products because of the recent phase out of polybrominated diphenyl ether (PBDE) flame retardants. OPFRs have been widely detected in adults and have been linked to reproductive and endocrine changes in adult males. Carcinogenicity and damage to immunologic, neurologic and developmental systems have been observed in human cell lines. Young children are especially vulnerable to OPFR exposure, but little is known about exposure levels or exposure risk factors in this population. We examined parent-reported demographic and dietary survey data in relation to OPFR urinary metabolite concentrations in 15- to 18-month old toddlers (n = 41). OPFR metabolites were detected in 100% of subjects. The metabolite of TPP, diphenyl phosphate (DPP) was detected most commonly (100%), with TDCPP metabolite, bis(1, 3-dichloro-2-propyl) phosphate (BDCPP), detected in 85–95% of samples, and ITP metabolite, monoisopropylphenyl phenyl phosphate (ip-DPP), detected in 81% of samples (n = 21). Toddlers of mothers earning <$10, 000 annually had geometric mean DPP concentrations 66% higher (p = 0.05) than toddlers of mothers earning >$10, 000/year (7.8 ng/mL, 95% CI 5.03, 12.11 and 4.69 ng/mL, 95% CI 3.65–6.04, respectively). While no dietary factors were significantly associated with OPFR metabolite concentrations, results suggested meat and fish consumption may be associated with higher DPP and BDCPP levels while increased dairy and fresh food consumption may be associated with lower DPP, BDCPP, and ip-DPP levels. Research with larger sample sizes and more detailed dietary data is required to confirm these preliminary findings. Highlights: 100% of toddler urine contained organophosphate flame retardants metabolites. Maternal income impacted toddler diphenyl phosphate (DPP) concentrations. Toddler dietary factors were below level of significance but showed trends.